The Schaubühne Berlin under Thomas Ostermeier : reinventing realism - Boenisch, Peter M. (Methuen Drama engage, 2022)
On the 20th anniversary of artistic director Thomas Ostermeier's time at Berlin's Schaubühne Theatre, this important study reflects on the contribution the theatre has made to contemporary theatre, not just in Germany, but around the world.Ostermeier has kept extending and refining the important notion of German Regietheater (directors' theatre) with the Schaubühne Theatre being its internationally famous birthplace under the previous artistic direction of Peter Stein. Through doing so, the work produced at the Schaubühne has transgressed established divides of text-based and devised theatre, and blurred the borders between theatre and dance.Combining scholarly reflection with interview material, this essential collection investigates how theatre has been reinvented by the Schaubühne under Ostermeier's tenure, bringing together international theatre scholars such as Erika Fischer-Lichte, Marvin Carlson, Jitka Goriaux Pelechova, Benjamin Fowler, Ramona Mosse and Sabine Huschka. This study also considers productions by some of Ostermeier's past and present collaborators, such as Katie Mitchell, Falk Richter and Sasha Waltz.This edition also includes the first English translation of Schaubühne's original manifesto “The Mission” (1999); a contribution from Ostermeier's long-term co-director Jens Hillje; a contribution from Hans-Thies Lehmann on Falk Richter; and an interview with Thomas Ostermeier by Clare Finburgh Delijani. --